2016
DOI: 10.1590/s1980-6574201600030002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength and aerobic performance of wheelchair basketball players

Abstract: Abstract--The respiratory system has been described as a limiting factor in the performance of athletes. Therefore, the objective of this study was to evaluate the relationship between the respiratory muscle strength (RMS) and aerobic performance of wheelchair basketball players (WCBPs). We evaluated 19 male WCBPs who were divided into two groups: trunk control group (TCG) and without trunk control group (WTCG). All participants underwent a pulmonary function test, evaluation of maximal inspiratory (MIP) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Deterioration in aerobic performance post SCI is related to reduced inspiratory muscle strength. 3 Pereira 23 observed that 36% and 50% of aerobic performance tests were influenced by inspiratory muscle strength in without trunk control group and with trunk control group respectively in wheelchair basketball players. It is believed that respiratory muscle fatigue alters exercise performance via metaboreflex 13 in which there is accumulation of metabolites such as lactic acid in the respiratory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration in aerobic performance post SCI is related to reduced inspiratory muscle strength. 3 Pereira 23 observed that 36% and 50% of aerobic performance tests were influenced by inspiratory muscle strength in without trunk control group and with trunk control group respectively in wheelchair basketball players. It is believed that respiratory muscle fatigue alters exercise performance via metaboreflex 13 in which there is accumulation of metabolites such as lactic acid in the respiratory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Vrijednosti testa Maksimalan pas u ovom istraživanju se statistički ne razlikuju od istih vrijednosti vrhunskih košarkaša u kolicima (Gil et al, 2015). Isto tako, vrijednosti dinamometrije obije šake ispitanika ovog istraživanja se statistički ne razlikuju od istih vrijednosti vrhunskih košarkaša u kolicima (Ferreira et al, 2017), ali se razlikuju između igrača različitih pozicija, povreda i klasa (Gil et al, 2015).…”
Section: Diskusijaunclassified
“…The results of the present study share some similarities with a retrospective study, where authors concluded that patients with acute exacerbation of COPD had reduced inspiratory muscle strength compared with those with stable disease [ 13 ], which is why we did not include patients with acute exacerbation of COPD in this study. Another study done by Pereira RN et al on wheelchair basketball players investigated the relationship between respiratory muscle strength and aerobic performance [ 14 ]. There was no significant correlation between the MIP and aerobic performance of the players, as determined by the 12-minute aerobic test.…”
Section: Discussionmentioning
confidence: 99%